Interdiscursivity in leadership discourse - Idris Aman,; Mohammad Fadzeli Jaafar, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2006)
Language is salient and important in the leadership process. Language in terms of 'discourse' has always been manipulated to achieve the final aims of a leader. A major part of the discourse that is related to the importance of language is its production, or discursive practice. This paper discusses how leadership discourse (or language use) is constructed, produced, and used in order to reach people for the sake of gaining continuous support. One form of discursive practice analyzed here is interdiscursivity or discourse type. This paper describes and interprets the 1982-1999 New Year messages of the fourth Malaysian's Prime Minister, Mahathir Mohamad. The discourse can be considered as institutional discourse. It is found that the leadership discourse is constructed and produced with the utilization of at least four discourse types, namely report, explanation, argumentation and expression. The four-discourse types are expository, informative,argumentative, and expressive in nature. In other words, the interdiscursivity of the fourdiscourse types is to inform, explain, argue or defend, and expresses the idea ofleadership of the addresser respectively. The end objective of such leadership discourse is to ensure that the addressee knows, understands, believes, and comes together in the leadership process of the addresser